If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14z + -5 = 2z + -65 Reorder the terms: -5 + 14z = 2z + -65 Reorder the terms: -5 + 14z = -65 + 2z Solving -5 + 14z = -65 + 2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2z' to each side of the equation. -5 + 14z + -2z = -65 + 2z + -2z Combine like terms: 14z + -2z = 12z -5 + 12z = -65 + 2z + -2z Combine like terms: 2z + -2z = 0 -5 + 12z = -65 + 0 -5 + 12z = -65 Add '5' to each side of the equation. -5 + 5 + 12z = -65 + 5 Combine like terms: -5 + 5 = 0 0 + 12z = -65 + 5 12z = -65 + 5 Combine like terms: -65 + 5 = -60 12z = -60 Divide each side by '12'. z = -5 Simplifying z = -5
| 1/5(10x-1)=5 | | -16x=-256 | | p=-0.5x^2+16-12 | | 62x=-248 | | -6u+49=6u | | 5x-15=2n+6 | | -37+x=-19 | | x^2+26x+153=0 | | r=0.766 | | 14+19x=195 | | 60x=-360 | | 8+(2x)=12 | | 2y=0-0 | | -12=11x-45 | | -7/3x-5y | | 32x-435=179 | | 2y=0-(-6) | | x-41=-48 | | -5/6x-4(3/8x+5/4y) | | x-48=-48 | | 3t+2s+4t+1s= | | 2y=0-(-2) | | -1y=0x+10 | | 87-x=135 | | 6(2x)-48=0 | | 2n+6=n+8 | | 2y=0-6 | | x^3+1/8 | | (4x+3)(3y-8)= | | 0x-2y=6 | | 356+56x=-832 | | 2s^2=50 |